Chapter 15. Drug Information and Literature Evaluation (Evidence-Based Pharmacotherapy in Clinical Practice, 2025)
AuthorDr. Surya Anusha Venna R Assistant Professor, Gokaraju Rangaraju College of Pharmacy, Hyderabad, Telangana, IndiaAbstractDrug information analysis requires systematic approaches to resource utilization and literature evaluation for clinical decision support. Information resource selection follows hierarchical assessment of evidence quality, currency, and clinical applicability. Literature search strategies utilize structured methods incorporating controlled vocabulary terms and systematic review of multiple databases. Study design evaluation incorporates assessment tools for specific research methodologies with emphasis on internal validity and generalizability. Statistical analysis interpretation focuses on clinical significance determination through effect size estimation and confidence interval evaluation. Application to practice requires integration of evidence quality assessment with patient-specific factors and practical implementation considerations. Systematic approaches incorporate regular updates of drug information resources, critical evaluation of new evidence, and modification of clinical protocols based on emerging dataKeywords: Literature evaluation, Information resources, Research methodology, Statistical interpretation, Evidence applicationVIEW PDF